HLA-B*57:01 allele prevalence in HIV-infected North American subjects and the impact of allele testing on the incidence of abacavir-associated hypersensitivity reaction in HLA-B*57:01-negative subjects. - Small, Catherine Butkus; Margolis, David A.; Shaefer, Mark S.; Ross, Lisa L. (BMC Infectious Diseases, 2017)
Background: The presence of the HLA-B*57:01 allele in HIV-infected subjects is associated with a higher risk of abacavir-associated hypersensitivity reaction (ABC HSR). HLA-B*57:01 allele prevalence varies in different populations, but HLA-B*57:01 testing with immunological confirmation has had a negative predictive value for ABC HSR between 97 and 100%.Methods: In the ASSURE study (EPZ113734), the HLA-B*57:01 prevalence in virologically suppressed, antiretroviral treatment-experienced, HIV-infected subjects from the United States, including Puerto Rico, was assessed.Results: Three hundred eighty-five subjects were screened; 13 were HLA-B*57:01 positive and 372 were negative. Only HLA-B*57:01-negative, abacavir-naive subjects were eligible to enroll into the ASSURE trial. Eleven of the 13 subjects who possessed the HLA-B*57:01 allele were white, the other 2 were African-American. There was no geographic clustering of HLA-B*57:01-positive subjects, and the incidence correlated roughly with those states with the greatest numbers of subjects screened. Similarly, there was no statistically significant correlation between subjects who possessed or lacked the allele and age, gender, ethnicity or CD4+ T-cell numbers. The incidence of ABC HSR following abacavir initiation was also evaluated. Only 1 of 199 HLA-B*57:01-negative subjects (an African-American male) randomized to receive abacavir-containing treatment developed symptoms consistent with suspected ABC HSR; ABC HSR was not immunologically confirmed.Conclusions: These findings confirm the utility of HLA-B*57:01 allele testing to reduce the frequency of ABC HSR. The prevalence of HLA-B*57:01 positivity was higher in white than in African-American subjects. In HLA-B*57:01-negative subjects, suspected ABC HSR is very rare, but should lead to discontinuation of abacavir when ABC HSR cannot be definitively excluded from the differential diagnosis.Trial Registration: The ASSURE (EPZ113734) study was registered on ClinicalTrials.gov registration on April 8th 2010 and the registration number is NCT01102972.